The Bidirectional Signal Communication of Microbiota-Gut-Brain Axis in Hypertension - Xiaoqi Wang; Zhenzhen Chen; Bin Geng; Jun Cai (International Journal of Hypertension)
Hypertension is a critical risk factor of cardiovascular diseases. A new concept of microbiota-gut-brain axis has been established recently, mediating the bidirectional communication between the gut and its microbiome and the brain. Alterations in bidirectional interactions are believed to be involved in the blood pressure regulation. Neuroinflammation and increased sympathetic outflow act as the descending innervation signals from the brain. Increased sympathetic activation plays a recognized role in the genesis of hypertension. The present evidence demonstrates that gut dysbiosis is associated with central nervous system neuroinflammation. However, how the gut influences the brain remains unclear. We reviewed the roles of neuroinflammation and gut microbiota and their interactions in the pathogenesis of hypertension and described the ascending signaling mechanisms behind the microbiota-gut-brain axis in detail. Additionally, the innovative prohypertensive mechanisms of dietary salt through the microbiota-gut-brain axis are summarized. The bidirectional communication mechanisms were proposed for the first time that the descending signals from the brain and the ascending connections from the gut form a vicious circle of hypertension progression, acting as a premise for hypertension therapy.